Efektivitas Citicoline sebagai Agen Neuroprotektif dalam Tata Laksana Traumatic Brain Injury - Bhirau Wilaksono; Andi Weri Sompa (PT Kalbe Farma Tbk., 2023)
Background: Traumatic brain injury (TBI) is a condition resulting from physical trauma to the head which can cause structural damage to the brain and interfere with cognitive, motor and emotional functions. Citicoline is a natural compound that plays an important role in phospholipid metabolism and neurotransmitter synthesis in the brain. This evidence-based case report (EBCR) study aims to provide scientific evidence of the potential benefits of citicoline in improving clinical outcomes in TBI patients. Method: Literature search using the PICO format. The formulation of clinical questions was arranged by case. Search for articles on March 6–7th 2023 using the Publish or Perish (PoP) software with the target of searching articles for the last 10 years (2013-2023) on the Scopus, Pubmed, Google Scholar databases, and manual searches on the Cochrane database, using the keyword 'traumatic brain' injury' AND 'therapy' AND 'citicoline' AND 'neuroprotective' AND 'treatment' AND 'outcome' along with synonyms and related terms. Results: Four studies were obtained, with the level of evidence 1a which resulted from a meta-analysis or systematic review of various randomized controlled trials, which were then critically reviewed. Two studies reported no significance of clinical assessment and the Glasgow Coma Scale (GCS); two other studies showed significant results at the level of independence. Conclusion: This study shows that citicoline is beneficial in the independence of TBI patients but does not produce a significant difference in the Glasgow Coma Scale assessment.